Роль самостійної роботи в процесі саморозвитку студентів - Канівець, Марина Вікторівна (НТУ "ХПІ", 2012)
The role and the relevance of the self-reliant work in the self-development process of a student during his study at the high school are identified in the article. Authors propose effective techniques for its activization. Main goals of a teacher in the management process of student's self-reliant work are stated. Article contains results of the exploration that is devoted to the study of role of self-reliant work in the personal self-development and determination of the student's preparation level for it.
Keywords: самостійна робота; саморозвиток; самоефективність; рефлексія; портфоліо